MATHEMATICAL MODELING OF PROCESSES OF MANAGEMENT OF URBAN PASSENGER TRANSPORT - T.U. BAZUK (Advanced Engineering Research)
On the data on quantity of the including and left passengers at each stop of all route the method of definition of the passenger correspondence by a settlement way and on the basis of the received researches the software is offered.